SCHOOL AS A KNOWLEDGE - BASED ORGANIZATION - GAJDA, Joanna (Trends in education, 2012)
Knowledge is a basic resource of each learning organization, only because of its basic one can be determine by main elements of the management system strategy. A clear condition both survival and development for each school is an infinite process of self - improvement, achieved on manner of searching for new methods, which may be achieved by taking advantage of and understanding - the knowledge. Both skills and a high level of knowledge allow for participating in a wider environment; consequently become unique and win new clients alike as partner organization.
Keywords: process of change; a change for the better; gain of workers; experience.